On the reproduction of capitalism : ideology and ideological state apparatuses / Louis Althusser ; preface by Etienne Balibar ; introduction by Jacques Bidet ; translated by G.M. Goshgarian. - Althusser, Louis, 1918-1990 (Verso, 2014)
What is perhaps Louis Althusser's most famous text, 'Ideology and Ideological State Apparatuses,' published in 1970 and very influential ever since, was an extract of a much longer book published in French years after his death. Published now for the first time in English, 'On the Reproduction of Capitalism' develops systematically Althusser's conception of historical materialism, outlining the conditions of reproduction in capitalist society and the revolutionary struggle for its overthrow.